Characterization of Arc Plasma by Movable Single and Double Langmuir Probes. (19th May 2019) - Thakur, Ghanshyam; Khanal, Raju; Narayan, Bijoyendra
Abstract: In this work, plasma is produced by arc discharge between two copper electrodes and is characterized by a movable single probe and a double Langmuir probe. The movable Langmuir single-probe technique has a reference point since it is biased with reference to one of the electrodes of the plasma-producing system. In some situations such as radio-frequency discharges, no reference point is available to bias the movable single probe. In the double-probe method, each probe is biased with respect to each other and allowed to move through the arc plasma. Depending on the magnitude of the biasing potential, charges are collected by the probes, and the probe current flowing to the circuit is calculated. After that, we obtain the electron temperature and plasma density of the arc plasma. By using the double-probe method, the value of the plasma density is more precise than with the single-probe method. Hence, the double-probe method is more appropriate than the single-probe method.